Selective enrichment of fractions in thermal dissolution of high-sulfur coal: Application of solid-phase microextraction technology and construction of ZnO/rGO coatings - Jia-Qi Liu; Xing Fan; Ran-Ran Hou; Xiao-Hui Cao; Binoy K. Saikia; Chao Feng; Jin-Xi Wu; Xiao-Yu Dong (Fuel, 2026)

Institutional configurations and conservation agriculture outcomes: A fuzzy-set analysis of production units in Lishu County, China's black-soil region - Hongwei Yu; Yufeng Hou; Youchao Xing; Huixin Ran; Chuanling Xiang; Mingze Xia; Zijie Liu; Hu Zhou (Land Use Policy, 2026)

Potassium oxalate-activated bamboo charcoal: a green solution for constructing high-performance capacitive deionization electrodes for nitrate removal - Weilong Xiao; Rencheng Li; Ming Gao; Ran Li; Luwei Miao; Yufeng Da; Yang Bao; Ke Li; Tianqi Ao; Qiulin Yang; Xing Chen; Haiyan Mou; et al. (Desalination, 2026)

Ultra small RuNi clusters synergistically promotes water dissociation and hydrogen adsorption for efficient hydrogen evolution in AEM water electrolyzers - Hongwei Zhao; Hongyi Li; Tianjiao Lou; Guangshun Ran; Hui Song; Xing Cheng (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

WTAP upregulates HK2 expression via m6A methylation to reprogram cell glycolysis and stemness under Cr(VI) exposure - Yunxia Xie; Lin Wang; Ruike Zhang; Wenwen Ran; Bing-Hua Jiang; Xiaoming Xing (Journal of Environmental Sciences, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

Experimental and theoretical research on the impact resistance performance of thin-walled viscoelastic vibration isolation devices - Juncheng Yao; Zhao-Dong Xu; Xing-Huai Huang; Jingbo Song; Fengfeng Ran; Xiaoning Mo; Jianchun Li; Zhongwen Pan (Soil Dynamics and Earthquake Engineering, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

Glycine regulates in vitro nutrient sensing of porcine oocytes through AMPK-mTORC1 - Ning Xu; Ran Teng; Xingfu Chen; Yuening Xing; Xiaoqing Sun; Dexin Yuan; Suo Li (Theriogenology, 2026)

Critical review of the influence of charge-assisted hydrogen bonding on fate, transport, and treatment of representative contaminants of emerging concern and natural organic matter - Xiaoyun Li; Yue Wang; Baoshan Xing; Marc Teixidó; María A. Cruz; Ran Wei; Jinzhi Ni; Hirotatsu Murano; Zhengyang Wang (Journal of Hazardous Materials, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Simulation of Extreme Weather Events in the Wanzhou Region of the Three Gorges Reservoir Area Using the WRF Model Coupled With Machine Learning Techniques - Yulin Zhou; Lang Xu; Xing Wei; Ruibo Shi; Yuanjun Chen; Libo Ran (International Journal of Climatology, 2026)
Accurate climate modelling and prediction are essential for understanding climate change impacts, optimising water resource management, and mitigating drought and flood risks. However, simulations of extreme precipitation and high‐temperature events remain highly uncertain due to the strong sensitivity of regional climate models to physical parameterisation schemes and the lack of systematic identification of optimal scheme combinations, particularly in regions characterised by complex terrain and reservoir regulation. To address this gap, this study systematically evaluates the performance of the Weather Research and Forecasting (WRF) model under multiple physical parameterisation schemes for extreme precipitation and high‐temperature events in the Wanzhou District of the Three Gorges Reservoir region. The optimal schemes are identified based on a comprehensive assessment of temporal and spatial consistency indices, error statistics, and agreement between simulations and observations. In addition, extreme gradient boosting (XGBoost), random forest (RF), and long short‐term memory (LSTM) models are applied to optimise WRF outputs through post‐processing. The results show that Scheme A5 (WSM6‐GD‐Noah‐RRTM/Dudhia) provides the best overall performance for extreme precipitation simulations, while Scheme B5 (WSM6‐GD‐Noah‐RRTMG/CAM) performs best for high‐temperature events. Furthermore, coupling the optimal WRF configurations with the RF model yields the greatest improvement, increasing the temporal and spatial consistency indices by 38.03% and 57.30% for extreme precipitation, and by 25.25% and 55.79% for high‐temperature events, respectively. The integration of machine learning models into WRF substantially improved the accuracy and reliability of extreme event predictions, providing vital scientific evidence and technical support for disaster risk reduction and meteorological forecasting in the Wanzhou District of the Three Gorges Reservoir region, thereby contributing to the sustainable development of regional environments and socioeconomics.

Phenoxyl radical-mediated peroxymonosulfate activation for efficient water remediation - Zhuan Chen; Yan Bao; Maoxi Ran; Jiayi Wang; Jiazhen Cao; Daqing Jia; Mingyang Xing (Water Research, 2026)

IP3R1 regulates AMPK-mTOR-mediated mitochondrial function to influence the oocyte-to-embryo transition of porcine - Ran Teng; Ning Xu; Xingfu Chen; Yuening Xing; Xiaoqing Sun; Dexin Yuan; Keming Huang; Lepeng Gao; Suo Li (Theriogenology, 2026)

Discovery of natural Nopol as promising antibacterial alternative with the capacity to suppress bacterial virulence and enhance plant immunity - Xiao-Di Chen; Yu-Mei Feng; Jun-Ning Ran; Wei Niu; Xin-Ming Yang; Xing-Yu Chen; Xiang Zhou; Song Yang (Pesticide Biochemistry and Physiology, 2026)

Interactive effects of noise and odor on construction workers' environmental perception and cognitive performance amid outdoor thermal stress - Zi Li; Xinyue Zhang; Zijing Peng; Ran Xing; Ang Li; Bo Hong (Building and Environment, 2026)

Toxoplasma GRA72 is Involved in Membrane-Associated Functions and Metabolic Homeostasis Revealed by Transcriptomic Analysis - Xin-Sheng Lu; Xing Tian; Jing Li; Chen-Ran Tian; Xing-Quan Zhu; Xiao-Nan Zheng (Acta Parasitologica, 2026)

Speciation-dependent bioaccessibility of lead in e-waste dismantling soils: Synchrotron spectroscopy reveals molecular controls across physiological compartments - Jian Liu; Yi-Fan Li; Yi-Heng Wang; Dong-Xing Guan; Hao-Ran Guan; Yi-Ren Li; Xing-Mei Liu (Journal of Hazardous Materials, 2026)

Decoding the molecular complexity of coal: A machine learning framework for component classification and solvent selection - Yu-Ying Zhou; Xing Fan; Jin-Xi Wu; Zhen-Yu Gao; Ran-Ran Hou; Chao Feng; Zhong-Qiu Liu; Qing Liu; Xiao-Yu Dong; Peng Liang (Fuel, 2026)

Emissions of nitrogen oxide from household gaseous cooking - Yongqiang Zhang; Jian Fu; Tianyao Huang; Jieyang Gao; Hanchen Wang; Ke Jiang; Ran Xing; Guofeng Shen; Shu Tao (Environmental Pollution, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Cross-scale modeling of bacteria-contaminant spatiotemporal dynamics in 3D bioprinted hydrogel for dye biodegradation - Weihao Guo; Ya-Nan Hou; Wei Xing; Ran Xu; Jinfeng Ma; Ai-Jie Wang; Nanqi Ren; Cong Huang (Bioresource Technology, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Sexual Dimorphism of Dendritic Spine Plasticity in the Cortex of Adolescent Mice - Fujian Qi; Yanli Ran; Guodong Zhu; Wancong Ding; Xing Gao; Junru Liu; Muhammad Tariq Hafeez; Huatai Xu; Shengxiang Zhang (Neuroscience Bulletin, 2026)

Unveiling TNFRSF19: a novel tumor suppressor targeting endoplasmic reticulum stress and LGR5/Wnt/β-catenin in cervical cancer - Xing Wei; Lili Su; Ran Chen; Tingting He; Changyi Wu (Human Cell, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Homo longi, Denisovans, Neanderthals and other archaic hominins in eastern Asia prior to the rise of Homo sapiens - Jingkun Ran; Huan Xia; Song Xing; Hao Li; Fahu Chen (Science Bulletin, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Low-temperature mineral engineering stabilizes anchored cobalt sites for ultrafast antibiotic destruction via electron transfer-driven radical/nonradical synergy - Liyao Ren; Ran Liu; Runbin Zeng; Lingling Cao; Wenyu Wang; Xuguang Li; Xing Xu; Yanxia Zhao; Liangguo Yan; Yanfei Li; Wen Song (ENGINEERING Environment, 2026)

Hydrogeochemical characteristics and controlling factors of groundwater in a typical oasis in arid regions - Xing Wei; Qingmei Zhang; Yulin Zhou; Libo Ran; Delun Chen; Xueting Dou; Yanan Fu; Gang Wu (Acta Geophysica, 2026)

Interfacial chemistry–stabilized GO coating on Cu substrate for durable lubrication - Peng Chen; Yilong Liang; Xichang Shang; Hui Zhang; Guanyu He; Xianli Ren; Xing Ran (Chemical Engineering Journal, 2026)

Spatiotemporal Variation Analysis of Yangtze River Basin Water Quality in Chong Qing, China During 2021–2023 Based on Improved Water Quality Assessment - Libo Ran; Xing Wei; Yulin Zhou; Qingmei Zhang; Yanan Fu; Zikan Deng (Water, Air, & Soil Pollution, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

Quasi-individual-level analysis of urban green space accessibility: Disparities, determinants, and equity across neighborhoods - Chenyu Fang; Mei-Po Kwan; Lin Zhou; Ran Chen; Xing Liu; Shidong Ge (Urban Forestry & Urban Greening, 2025)

Can urban-rural public services drive the realization of sustainable development goals? An empirical study of a typical rural‒urban integration pilot area in China - Huiping Ran; Rui Liu; Li Xing; Yifei Zhao; Kunlian Zhang (Journal of Rural Studies, 2025)

Reservoirs enhance bacterial diversity but destabilize microbial co-occurrence network compared to natural lakes: A global meta-analysis - Lei Zheng; Yaoxin Zhang; Qiuyang Tan; Xue Wang; Yuzi Xing; Qi Tian; Ran Tao; Haozhe Zhang (Journal of Hydrology, 2025)

The coexistence of Bacillus haynesii and Bacillus tequilensis achieves synchronous algicidal activity and denitrification and enhances the MC-LR degradation of phycosphere microbiota - Yuzi Xing; Lei Zheng; Zixuan Li; Guizhen Hao; Xue Wang; Ran Tao; Qi Tian; Yaoxin Zhang; Haozhe Zhang (Journal of Hazardous Materials, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Chemical and Isotopic Characteristics of Groundwater in Typical Cities of Three Gorges Reservoir Area in China and Its Suitability for Agricultural Irrigation - Xing Wei; Libo Ran; Yulin Zhou; Mengen Chen; Kaiyu Jiang; Yanan Fu (Water, Air, & Soil Pollution, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Piezo-photocatalytic-Fenton-like ternary coupling system for enhanced resourceful conversion of organic pollutants - Maoxi Ran; Yunkai Hu; Jiazhen Cao; Yue Jiang; Mingyang Xing (Water Research, 2025)

Chitosan and its functional derivatives for nutraceutical delivery: Focus on quaternized, hydrochloride, and carboxymethyl forms - Lu Zhang; Yanqing Zhang; Wei Li; Yingxin Zhou; Ran Guo; Xing Pei; Junbo Xie (Trends in Food Science & Technology, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Selective electroreduction of carbon dioxide to ethylene over stable iodide-induced asymmetric copper sites within a metal-organic polyhedron - Yaguang Peng; Yinlin Chen; Zi Wang; Yaoyu Yin; Jiangnan Li; Huanyan Liu; Jiapeng Jiao; Wenling Zhao; Ran Duan; Pei Zhang; Jiahao Yang; Hengan Wang; et al. (Science Bulletin, 2025)

The Association of Blood Cobalt Levels with Cardiovascular and Chronic Kidney Diseases: Mediating Role of Inflammatory Indicators (SII, NLR, PLR, NMLR, and LMR) - Bei-Bei Lu; Qian Luo; Xiao-Lin Yuan; Qing-Song Chen; Jing-Yang Ran; Xing-Wei Zhe; Xiao-Hui Liao (Cardiovascular Toxicology, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Influence of UHT processing and storage on the gastrointestinal fate and bioavailability of bovine milk proteins - Xing Li; Xiuxiu Zhang; Ran Xiao; Tianjiao Niu; Yuxiang Gu (Food Bioscience, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

Trichothecenes with cytotoxic activity and benzene derivatives with hypolipidemic activity from trichothecium sp - Liang Xing; Yi-Fan Guo; Ke-Ran Hao; Yi-Ting Wu; An-An Yang (Natural Product Research, 2025)

Biodegradable and antibacterial edible films based on egg yolk granules/gelatin/CMC with e-poly-l-lysine: Application in fresh chicken meat preservation - Muhammad Moeid Khan; Shuguo Sun; Ran Shi; Lv Aichun; Ok-Hwan Lee; Xing Fu (Food Chemistry, 2025)

Comparison and mechanism analysis of fatty acid differences between backcross F2 derived from blunt snout bream (Megalobrama amblycephala,♀) × topmouth culter (Culter alburnus,♂) and its closely related species - Qixiang Wang; Haoyang Wangchen; Junhan Luo; Yanling Qing; Ran Jiang; Yanan Luo; Xing Gao; Jing Liu; Zhenfeng Chen; Yanfang Li; Shenping Cao; Jianzhou Tang; et al. (Aquaculture International, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Advances and applications in single-cell and spatial genomics - Jingjing Wang; Fang Ye; Haoxi Chai; Yujia Jiang; Teng Wang; Xia Ran; Qimin Xia; Ziye Xu; Yuting Fu; Guodong Zhang; Hanyu Wu; Guoji Guo; et al. (Science China Life Sciences, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Assessment of high-position glacial valleys in Southeast Tibet, China: an integrated approach using remote sensing, UAV, field investigation, and numerical simulation - Congyan Ran; Shishu Zhang; Xinfu Xing; Haizhu Qu; Zhanglei Wu; Da Zheng; Zhenhui Pan; Maohong Yao; Kai Zhang (Natural Hazards, 2025)

Assessing river-blocking risks of ancient landslide in mountainous regions: insights from a slow-moving, high-position reactivated ancient landslide in the Southeast Tibetan Plateau - Xinfu Xing; Changbao Guo; Tanfang Zhu; Peng Xin; Hao Yuan; Yiqiu Yan; Congyan Ran (Bulletin of Engineering Geology and the Environment, 2025)

Fine-particle separation in heavy metal soil remediation using innovative hydrocyclone technology - Ruiqi Zhang; Leyao Xing; Yang Li; Ran Shen; Jixian Yang; Lixin Gao (Science of The Total Environment, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Interface Enhancement of skin electrodes with vertical gold Nanowires-based interlocking layers for wearable electrophysiological recording - Haiyue Zhang; Yiyang Shen; Lixiang Xing; Wenzhao Wang; Lihua Liu; Ran Jin; Ziyi He; Yiting Wang; Shuhua Yao; Xuan Cao; Shurong Dong; Bowen Zhu (Chemical Engineering Journal, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Magnetic polydopamine nanoparticles as stabilisers for enzyme-Pickering emulsions: Application in the interfacial catalytic reaction of olive oil - Ziqi Lin; Linhua Huang; Adil Mohamed Abker; Deog-Hwan Oh; Jihan Mohamed Kassem; Mohamed Salama; Ran Shi; Xing Fu (Food Chemistry, 2025)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Fractions of smoke leakage into indoor space from residential solid fuel combustion in chimney stoves - Zhihan Luo; Tianyao Huang; Yatai Men; Ran Xing; Yaojie Li; Ke Jiang; Kai Xiao; Guofeng Shen (Environmental Pollution, 2024)

Spatiotemporal Characteristics of Atmospheric Brown Carbon Emission from Combustion Sources in China - Shuyu Ouyang; Ke Jiang; Rui Xiong; Yatai Men; Zhihan Luo; Ran Xing; Guofeng Shen (Chinese Geographical Science, 2024)

Effects of plastic aging on biodegradation of polystyrene by Tenebrio molitor larvae: Insights into gut microbiome and bacterial metabolism - Meng-Qi Ding; Jie Ding; Shan-Shan Yang; Xin-Ran Ren; Shao-Nan Shi; Lu-Yan Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Science of The Total Environment, 2024)

A dual mechanism drives the enrichment of pedogenic magnetic particles derived from red beds - Ran Huang; Xiaoyong Long; Yue Zhang; Dengchun Xing; Chuan Liu; Yongjun Jiang; Daoxian Yuan (CATENA, 2024)

Combining GC–MS/MS with a LLE-SPE sample pretreatment step to simultaneously analyse enrofloxacin and ofloxacin residues in chicken tissues and pork - Maoda Pang; Junjie Xu; Yayun Tang; Yawen Guo; Hao Ding; Ran Wang; Tao Zhang; Genxi Zhang; Xiaodong Guo; Guojun Dai; Xing Xie; Kaizhou Xie (Food Chemistry, 2024)

Effect of pasteurization and storage on the bioavailability of milk proteins during in vitro intestinal digestion and Caco-2 cell transport - Xing Li; Ran Xiao; Shudong He; Yuxiang Gu; Tianjiao Niu (Food Bioscience, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

A TMSBL underwater acoustic channel estimation method based on dictionary learning denoising - Chuanxi Xing; Yanling Ran; Mao Lu; Guangzhi Tan; Qiang Meng (Frontiers in Marine Science, 2024)
The shallow sea underwater acoustic channel exhibits a significant sparse multipath structure. The temporally multiple sparse Bayesian learning (TMSBL) algorithm can effectively estimate this sparse multipath channel. However, the complexity of the algorithm is high, the signal-to-noise ratio (SNR) of shallow-sea underwater acoustic communication is low, and the estimation performance of the TMSBL algorithm is greatly affected by noise. To address this problem, an improved TMSBL underwater acoustic channel estimation method based on a dictionary learning noise reduction algorithm is proposed. Firstly, the K-Singular Value Decomposition (K-SVD) dictionary learning method is used to reduce the noise of the received pilot matrix, reducing the influence of noise on the signal. Then, the Generalized Orthogonal Matching Pursuit (GOMP) channel estimation method is combined to obtain a priori information such as the perceptual matrix and hyperparameter matrix for TMSBL channel estimation; and the noise variance is obtained by using the null subcarrier calculation instead of iteratively updating the noise variance in the TMSBL, to improve the estimation accuracy and reduce the algorithmic complexity. Finally, the TMSBL channel estimation method is used to estimate the underwater acoustic channels of different symbols jointly. The simulation results show that the normalized mean square error of the channel estimation of the improved TMSBL method is reduced by about 92.2% compared with the TMSBL algorithm, obtaining higher estimation accuracy; running time is reduced by about 45.6%, and there is also better performance in terms of the running speed, which provides a reference for underwater acoustic channel estimation.

Efficient and low-energy degradation of chlorobenzene via catA-mediated cleavage and bedC1 docking in a novel Burkholderia stabilis TF-2 - Zhilin Xing; Fang Gou; Xiaoping Zhang; Yanhui Gao; Xihong Ke; Dongni Ran; Peng Wang; Jiangfeng Guo; Heng Wu; Chao Peng; Tiantao Zhao (Chemosphere, 2024)

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Energy-economy-environment assessment of key feedstock production for ternary lithium-ion batteries via hydrometallurgical recycling and natural exploitation - Kai Wang; Quanshui Huang; Ran Feng; Shaojun Liu; Peng Xing; Zi-Tao Yu; Qingyang Lin; Xiang Gao (Journal of Cleaner Production, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

The properties of Chinese Baijiu distilled spent grain-derived hydrochar: effect of in situ deep eutectic solvents formation during hydrothermal carbonization - Huan-Ran Xiong; Fan Gao; Yi Tan; Yong-Xing Chen; Zhi-Xiang Xu (Journal of Environmental Chemical Engineering, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Intraseasonal variability of the deep scattering layer induced by mesoscale eddy - Bei Wang; Fei Yu; Ran Wang; Zhencheng Tao; Qiang Ren; Xing Chuan Liu; Jian Feng Wang (Frontiers in Marine Science, 2024)
The deep scattering layer (DSL), a stratum of the marine diel vertical migration (DVM) organisms inhabiting the mesopelagic ocean, plays a crucial role in transporting carbon and nutrients from the surface to depth through the migration of its organisms. Using 18 months of in-situ observations and altimeter sea level data, we reveal for the first time the intraseasonal variations and underlying mechanisms of the DSL and the DVM to the east of the Taiwan Island. Substantial vertical speeds acquired from the Acoustic Doppler Current Profiler were used to examine the distribution and variation of the DVM. Innovatively, the results for the power spectrum analysis of the scattering intensity demonstrated a significant intraseasonal variability (ISV) with an 80-day period in the DSL. Furthermore, the variation in the DVM was closely linked to the DSL and showed an 80-day ISV during the observation. A dynamic relationship between the ISV of the DSL east of Taiwan Island and the westward-propagating mesoscale eddies was established. Anticyclonic (cyclonic) eddy movement toward Taiwan Island triggers downward (upward) bending of the local isotherms, resulting in a layer of DSL warming (cooling) and subsequent upper boundary layer deepening (rising). These findings underscore the substantial influence of mesoscale eddies on biological activity in the mesopelagic ocean, establishing a novel understanding of ISV dynamics in the DSL and their links to eddy-induced processes.

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

KDM4B down-regulation facilitated breast cancer cell stemness via PHGDH upregulation in H3K36me3-dependent manner - Xin-Yu Wang; Hong-Ming Li; Ran Xia; Xiang Li; Xing Zhang; Tong-Zhao Jin; Hong-Sheng Zhang (Molecular and Cellular Biochemistry, 2024)

The famine of the Ming Dynasty in Shaanxi Province, China - Xing Gao; Ran An; Ge Gao; Peiwei Li (Regional Environmental Change, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

Elimination of antibiotic-resistant bacteria and resistance genes by earthworms during vermifiltration treatment of excess sludge - Meiyan Xing; Ran Zhao; Gege Yang; Zhan Li; Yuzhu Sun; Zitao Xue (Environmental Science and Pollution Research, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Nitrogen source affects non-aeration microalgal-bacterial biofilm growth progression and metabolic function during greywater treatment - Jiake Li; Beibei Wu; Meng Xu; Xuan Han; Yinuo Xing; Yu Zhou; Mengyao Ran; Yun Zhou (Bioresource Technology, 2024)

Cyclic Impact Damage and Water Saturation Effects on Mechanical Properties and Kaiser Effect of Red Sandstone Under Uniaxial Cyclic Loading and Unloading Compression - Kui Zhao; Lin Zhang; Daoxue Yang; Jiefang Jin; Peng Zeng; Xing Wang; Shanhu Ran; Dongming Deng (Rock Mechanics and Rock Engineering, 2024)

Modeling China's terrestrial ecosystem gross primary productivity with BEPS model: Parameter sensitivity analysis and model calibration - Xiuli Xing; Mousong Wu; Wenxin Zhang; Weimin Ju; Torbern Tagesson; Wei He; Songhan Wang; Jun Wang; Lu Hu; Shu Yuan; Tingting Zhu; Xiaorong Wang; et al. (Agricultural and Forest Meteorology, 2023)

Trends in air pollutants emissions in the Qinghai-Tibet Plateau and its surrounding areas under different socioeconomic scenarios - Ke Jiang; Ran Xing; Zhihan Luo; Jin Li; Yatai Men; Huizhong Shen; Guofeng Shen; Shu Tao (Science of The Total Environment, 2023)

First pelagic fish biodiversity assessment of Cosmonaut Sea based on environmental DNA - Yuzhuo Liao; Xing Miao; Rui Wang; Ran Zhang; Hai Li; Longshan Lin (Marine Environmental Research, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Indoor exposure to polycyclic aromatic hydrocarbons associated with solid fuel use in rural China - Shiyin Li; Yatai Men; Zhihan Luo; Wenxuan Huang; Ran Xing; Chao Sun; Guofeng Shen (Environmental Geochemistry and Health, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Bacterial diversity in water from Xifeng Hot Spring in China - Lijuan Wu; Hong Long; Shihui Huang; Xi Niu; Sheng Li; Xing Yu; Longjiang You; Xueqin Ran; Jiafu Wang (Brazilian Journal of Microbiology, 2023)

Species identification of culinary spices with two-locus DNA barcoding - Meng-Yue Zhou; Ran-Ran Xing; Ke-Han Liu; Yi-Qiang Ge; Ying Chen (Food Control, 2023)

Strategic tillage is a promising alternative to conventional and no-tillage: Evidence from a 12-year field trial in a double-cropped rice system - Xing Wang; Cong He; Bai-Jian Lin; Xin Zhao; Ran Zhang; Ling-Tao Zhong; Xiao-Ping Xiao; Hai-Lin Zhang (European Journal of Agronomy, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Selective removal of ultrafine suspended solids during organic pollutant degradation by a MoS2/graphene oxide sponge - Lingli Zhu; Qingyun Yan; Maoxi Ran; Xinyue Liu; Yan Bao; Xiaoguang Duan; Mingyang Xing (Science Bulletin, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Effects of Vertical Water Column Temperature on Distribution of Juvenile Tuna Species in the South China Sea - Shigang Liu; Yuan Li; Rui Wang; Xing Miao; Ran Zhang; Siyuan Chen; Puqing Song; Longshan Lin (Fishes, 2023)
In this study, we conducted two surveys in the central and southern parts of the South China Sea, in autumn 2012 and spring 2013. Six juvenile tuna species were caught in each survey. Gradient forest analysis (GFA) and a generalized additive model (GAM) were used to analyze the relationship between the catch per unit effort (CPUE) for the juvenile tuna species and six sea temperature indices for the South China Sea. In the GFA, the temperature difference between the sea surface and 50 m depth (D50) showed the highest importance to CPUE than other indices, which indicates that D50 was the best predictor of the abundance of juvenile tuna species. The GAM analysis showed that lower deep-water temperature, a shallow mixed layer depth, and a higher difference in temperature between the surface and deeper water were associated with increased CPUE. The results indicate that a relatively rapid decrease in vertical water temperature is favorable for the aggregation of juvenile tuna. These results contribute to understanding of the distribution mechanism of juvenile tuna species in the South China Sea and provide a scientific basis for the rational development and utilization of tuna resources.

Separation, quantification and characterisation of the pigment produced by Paecilomyces lilacinus TD16 - Xianyong Yu; Xiangying Xing; Qinglin Dong; Kangli Shi; Ran Yan (Natural Product Research, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

An improved approach to estimate ratoon rice aboveground biomass by integrating UAV-based spectral, textural and structural features - Le Xu; Longfei Zhou; Ran Meng; Feng Zhao; Zhengang Lv; Binyuan Xu; Linglin Zeng; Xing Yu; Shaobing Peng (Precision Agriculture, 2022)

DNA barcoding provides insights into Fish Diversity and Molecular Taxonomy of the Amundsen Sea - Shuai Cao; Yuan Li; Xing Miao; Ran Zhang; Longshan Lin; Hai Li (Conservation Genetics Resources, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Spatio-temporal characteristics of demersal fish community in the Chukchi and northern Bering Seas: significant distributional records and interannual variations in species composition and biodiversity - Ran Zhang; Puqing Song; Hai Li; Rui Wang; Yuan Li; Xing Miao; Longshan Lin; Shaoxiong Ding (Polar Biology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Correction to: Experimental study on strength properties, fracture patterns, and permeability behaviors of sandstone containing two filled fissures under triaxial compression - Tingchun Li; Yiteng Du; Qingwen Zhu; Jinlin Ran; Hao Zhang; Xueyang Xing (Bulletin of Engineering Geology and the Environment, 2021)

Experimental study on strength properties, fracture patterns, and permeability behaviors of sandstone containing two filled fissures under triaxial compression - Tingchun Li; Yiteng Du; Qingwen Zhu; Jinlin Ran; Hao Zhang; Xueyang Xing (Bulletin of Engineering Geology and the Environment, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Blocking of the PD-1/PD-L1 interaction by a novel cyclic peptide inhibitor for cancer immunotherapy - Wenjie Zhai; Xiuman Zhou; Mingxia Zhai; Wanqiong Li; Yunhui Ran; Yixuan Sun; Jiangfeng Du; Wenshan Zhao; Lingxiao Xing; Yuanming Qi; Yanfeng Gao (Science China Life Sciences, 2021)

Performances of six eupelmid egg parasitoids from China on Japanese giant silkworm Caligula japonica with different host age regimes - Yong-Ming Chen; Xing-Ran Qu; Tian-Hao Li; Asim Iqbal; Xingeng Wang; Zhi-Yong Ren; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2021)

Heterologous Expression of the Leuconostoc Bacteriocin Leucocin C in Probiotic Yeast Saccharomyces boulardii - Ran Li; Xing Wan; Timo M. Takala; Per E.J. Saris (Probiotics and Antimicrobial Proteins, 2021)
The yeast Saccharomyces boulardii is well known for its probiotic effects such as treating or preventing gastrointestinal diseases. Due to its ability to survive in stomach and intestine, S. boulardii could be applied as a vehicle for producing and delivering bioactive substances of interest to human gut. In this study, we cloned the gene lecC encoding the antilisterial peptide leucocin C from lactic acid bacterium Leuconostoc carnosum in S. boulardii . The constructed S. boulardii strain secreted a peptide, which had molecular weight corresponding to leucocin C in SDS-PAGE. The peptide band inhibited Listeria monocytogenes in gel overlay assay. Likewise, concentrated S. boulardii culture supernatant inhibited the growth of L. monocytogenes . The growth profile and acid tolerance of the leucocin C secreting S. boulardii were similar as those of the strain carrying the empty vector. We further demonstrated that the cells of the leucocin C producing S. boulardii efficiently killed L. monocytogenes , also without antibiotic selection pressure. These results showed that antilisterial activity could be added to the arsenal of probiotic activities of S. boulardii , demonstrating its potential as a carrier for therapeutics delivery.

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

Extracting tidal creek features in a heterogeneous background using Sentinel-2 imagery: a case study in the Yellow River Delta, China - Zhaoning Gong; Qiwei Wang; Hongliang Guan; Demin Zhou; Lei Zhang; Ran Jing; Xing Wang; Zhe Li (International Journal of Remote Sensing, 2020)

A threshold stresses-based permeability variation model for microcracked porous rocks - Xing Li; Yi-Feng Chen; Kai Wei; Ran Hu; Zhi-Bing Yang (European Journal of Environmental and Civil Engineering, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

The Effect of Selenium on the Cd-Induced Apoptosis via NO-Mediated Mitochondrial Apoptosis Pathway in Chicken Liver - Runxiang Zhang; Ran Yi; Yanju Bi; Lu Xing; Jun Bao; Jianhong Li (Biological Trace Element Research, 2017)

Assessment of metal contamination in the Hun River, China, and evaluation of the fish Zacco platypus and the snail Radix swinhoei as potential biomonitors - Xing Wu; Shaofeng Wang; Hongxing Chen; Zhiqiang Jiang; Hongwei Chen; Mi Gao; Ran Bi; Paul L. Klerks; He Wang; Yongju Luo; Lingtian Xie (Environmental Science and Pollution Research, 2017)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Hydrodynamic processes and depositional styles of glacier-associated deposits in the Moxi basin, Southwest China - Yong-bo Tie; Xing-lei Feng; Jing Ran; Wei Xu (Journal of Mountain Science, 2016)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Epigallocatechin-3-gallate induced primary cultures of rat hippocampal neurons death linked to calcium overload and oxidative stress - Shu-Ting Yin; Ming-Liang Tang; Hong-Min Deng; Tai-Ran Xing; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Effects of Cd2+ on transient outward and delayed rectifier potassium currents in acutely isolated rat hippocampal CA1 neurons - Shu Wang; Tai-Ran Xing; Ming-Liang Tang; Wu Yong; Chen-Chen Li; Liang Chen; Hui-Li Wang; Jiu-Lai Tang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Stress hormone and male reproductive function - Matthew P. Hardy; Hui-Bao Gao; Qiang Dong; Renshan Ge; Qian Wang; Wei Ran Chai; Xing Feng; Chantal Sottas (Cell and Tissue Research, 2005)